The Role of Global Longitudinal Strain in Detecting Early Left Ventricular Dysfunction in Pediatric Bicuspid Aortic Valve Patients - Mohammed A. Mashali; Isabelle Deschênes; Carl V. Leier; Nancy S. Saad (Children, 2025)
Global longitudinal strain (GLS), assessed via speckle tracking echocardiography (STE), is increasingly recognized as a sensitive and early indicator of left ventricular (LV) dysfunction in pediatric patients with bicuspid aortic valve (BAV) [...]